Positional Scanning Synthesis of a Peptoid Library Yields New Inducers of Apoptosis that Target Karyopherins and Tubulin. Issue 11 (17th June 2015) - Vendrell‐Navarro, Glòria; Rúa, Federico; Bujons, Jordi; Brockmeyer, Andreas; Janning, Petra; Ziegler, Slava; Messeguer, Angel; Waldmann, Herbert
Abstract We describe the synthesis of a library of 11 638 N‐alkylglycine peptoid trimers in a positional scanning format with adjustment of reaction conditions to account for different reactivities of the monomer building blocks. Evaluation of the library by high‐content phenotypic screening for modulators of the cytoskeleton and mitosis resulted in the identification of two apoptosis‐inducing peptoids, which, despite their structural similarity, target different proteins and cellular mechanisms. Whereas one peptoid binds to karyopherins, which mediate nuclear transport, the other N‐alkylglycine trimer binds tubulin at the vinca alkaloid binding site.